Multilinear Algebras and Tensors with Vector Subbundle of Manifolds - Ahmed, Khondokar M; Tahora, Saraban (Dhaka University Journal of Science, 2015)
In the present paper some aspects of tensor algebra, tensor product, exterior algebra, symmetric algebra, module of section, graded algebra, vector subbundle are studied. A Theorem 1.32. is established by using sections and fibrewise orthogonal sections of an application of Gran-Schmidt. DOI: http://dx.doi.org/10.3329/dujs.v62i1.21957 Dhaka Univ. J. Sci. 62(1): 31-35, 2014 (January)